2011
DOI: 10.1128/jvi.01616-10
|View full text |Cite
|
Sign up to set email alerts
|

North American Porcine Reproductive and Respiratory Syndrome Viruses Inhibit Type I Interferon Production by Plasmacytoid Dendritic Cells

Abstract: Although enveloped viruses typically trigger the prodigious secretion of alpha interferon (IFN-␣) by plasmacytoid dendritic cells (pDC), porcine pDC remain quiescent when exposed to porcine reproductive and respiratory syndrome virus (PRRSV). This inactivity is likely due to virus-mediated interference since the typical IFN-␣ response by either purified or nonsorted porcine pDC to transmissible gastroenteritis virus (TGEV) or the Toll-like receptor 9 agonist, oligodeoxynucleotide (ODN) D19, was markedly reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
77
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 77 publications
5
77
1
Order By: Relevance
“…Signature genes characteristic of the antiviral state include those involved in the activation of IRF-3/IRF-7 and stimulation of antiviral ISGs (2,7,10,12,15). Based on our studies and those of others, we know that induction of the antiviral state is common in all monocytic cells (2,10,17,18,21), but whether subsets of monocytes and Ms are preset for antiviral responses, such as pDCs showing a natural propensity of IFN-␣ production, is not known (11,24).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Signature genes characteristic of the antiviral state include those involved in the activation of IRF-3/IRF-7 and stimulation of antiviral ISGs (2,7,10,12,15). Based on our studies and those of others, we know that induction of the antiviral state is common in all monocytic cells (2,10,17,18,21), but whether subsets of monocytes and Ms are preset for antiviral responses, such as pDCs showing a natural propensity of IFN-␣ production, is not known (11,24).…”
Section: Resultsmentioning
confidence: 99%
“…Because deviation of the IFN system has been well demonstrated in PRRSV infection and is a potential target for antiviral regulation (7,10,12,13,15,21), we first analyzed DEGs related to the IFN system, particularly type I IFN production and action in macrophages at differential activation statuses. In pigs, PRRSV strains exerted differential ability to inhibit the production and action of type I IFNs, particularly in IFN-␣ rather than IFN-␤ subtypes (21)(22)(23)(24)(25)34). We previously showed that the swine genome contains at least 39 functional genes encoding 7 subtypes of type I IFNs, including multiple members of the IFNs IFN-␣, Ϫ⌬CT from infected cells were plotted against that from control cells to indicate up-or downregulation and to reflect the relative expression.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations